2013
DOI: 10.3892/etm.2013.1431
|View full text |Cite
|
Sign up to set email alerts
|

Expression of N-cadherin proteins in myocardial hypertrophy in rats

Abstract: The aim of the present study was to examine the expression of N-cadherin in the myocardial tissues of isoproterenol-induced myocardial hypertrophy in rats. In addition, the present study provided morphological data to investigate the signal transduction mechanisms of myocardial hypertrophy and reverse myocardial hypertrophy. A myocardial hypertrophy model was established by subcutaneously injecting isoprenaline into healthy adult Sprague-Dawley rats. The myocardial tissue was collected, embedded in conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…CDH2 comes from a superfamily of adhesion molecules that mediate Ca 2+ -dependent cell-to-cell adhesion in tissues [48]. In a model of myocardial hypertrophy, CDH2 was postulated as one of the mechanisms that enables the heart to maintain its physical structure and mechanical function by enhancing cell-to-cell contact and membrane connections [49]. Mitochondrial HSPA9 is a chaperone protein in the biogenesis and refolding of mitochondrial iron-sulfur proteins; it may also have a role in cell proliferation and cellular aging [46].…”
Section: Oxidative Stress (Hf Vs Con Diet): Supplemental Tablementioning
confidence: 99%
“…CDH2 comes from a superfamily of adhesion molecules that mediate Ca 2+ -dependent cell-to-cell adhesion in tissues [48]. In a model of myocardial hypertrophy, CDH2 was postulated as one of the mechanisms that enables the heart to maintain its physical structure and mechanical function by enhancing cell-to-cell contact and membrane connections [49]. Mitochondrial HSPA9 is a chaperone protein in the biogenesis and refolding of mitochondrial iron-sulfur proteins; it may also have a role in cell proliferation and cellular aging [46].…”
Section: Oxidative Stress (Hf Vs Con Diet): Supplemental Tablementioning
confidence: 99%
“…The expression of adhesion molecules including CD11a, CD11b and CD11c was increased in rats with myocardial hypertrophy. 115 Walsh reported that the inhibition of stress-induced activin A/Smad2 signalling triggered the expression of follistatin-like in hypertrophied cardiac myocytes. 116 Follistatin-like 3 is a stress-induced regulator of cardiac hypertrophy and may regulate myocyte size via Smad signalling.…”
Section: Other Moleculesmentioning
confidence: 99%